Japans Landwirtschaft auf dem Weg in den Nebenerwerb.: Eine sozialgeographische Analyse - Ishii, Motosuke (ERDKUNDE, 1980)
The change in the agrarian structure of post-war Japan is reflected amongst other things in a distinct turn of agriculture towards additional paid work, especially so during 1960 to 1975, the years of economic boom. Since this process shows differences in development with regard to time and place the attempt is made here to analyse the change in the agrarian structure with the aid of the key indicator development types of part-time agriculture. In this the Osaka area presents rings of increasing employment that advance outwardly with time. Moreover there were striking regional contrasts in the advance of part-time agriculture between eastern and western parts of the country. More detailed characteristics of the process are examined at regional level with the aid of indicators like urbanisation, type of under taking, and so on. In conclusion there is an examination of the advantages and disadvantages of the key indicator development types of part-time agriculture, in which the significance of the regional point of view and the usefulness of the cartographic method of analysis are stressed.